2022
DOI: 10.1021/acs.est.2c04736
|View full text |Cite
|
Sign up to set email alerts
|

Nanofiltration Membranes with Crumpled Polyamide Films: A Critical Review on Mechanisms, Performances, and Environmental Applications

Abstract: Nanofiltration (NF) membranes have been widely applied in many important environmental applications, including water softening, surface/groundwater purification, wastewater treatment, and water reuse. In recent years, a new class of piperazine (PIP)-based NF membranes featuring a crumpled polyamide layer has received considerable attention because of their great potential for achieving dramatic improvements in membrane separation performance. Since the report of novel crumpled Turing structures that exhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 135 publications
(45 citation statements)
references
References 214 publications
(418 reference statements)
3
42
0
Order By: Relevance
“…This trend is consistent with previous studies. ,, The increased permeance can be attributed to the enlarged nanovoids from TFC-0.2 to TFC-2 (see the TEM graphs in Figure ), which can be resulted from more generated nanobubbles by their higher MPD storage . Previous studies have shown that nanovoids are effective in improving the water transport pathways in TFC membranes due to their “gutter effect”. , On the other hand, the declined permeance for TFC-8 can be explained by its thicker polyamide film (see the TEM graphs in Figure ), which may offset the benefit of its larger nanovoids . The addition of TW generally improved the water permeance compared to TFC membranes (Figure a), thanks to the more prominent nanovoids of TFC–TW membranes (Figure ).…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…This trend is consistent with previous studies. ,, The increased permeance can be attributed to the enlarged nanovoids from TFC-0.2 to TFC-2 (see the TEM graphs in Figure ), which can be resulted from more generated nanobubbles by their higher MPD storage . Previous studies have shown that nanovoids are effective in improving the water transport pathways in TFC membranes due to their “gutter effect”. , On the other hand, the declined permeance for TFC-8 can be explained by its thicker polyamide film (see the TEM graphs in Figure ), which may offset the benefit of its larger nanovoids . The addition of TW generally improved the water permeance compared to TFC membranes (Figure a), thanks to the more prominent nanovoids of TFC–TW membranes (Figure ).…”
Section: Resultssupporting
confidence: 90%
“…We further found that TW addition could reduce membrane fouling propensity-the TFC–TW membrane experienced lower flux decline and less accumulation of HA on its surface compared to the TFC membrane (Figure a,b). The reduced fouling tendency can be attributed to the more prominent nanovoids in TFC–TW, which could potentially regulate the water transport and flux distribution above its polyamide film. ,, Interestingly, TFC shows much sharper flux decline than TFC–TW at the initial stage of fouling test, which can be ascribed to more defects in its polyamide layer. Since defects can result in hot spots of high-localized flux, foulants would preferentially deposit at these regions at the initial stage to accelerate membrane fouling. ,, It is worthwhile to note that the current study only investigated fouling tendency over relatively short filtration duration (96 h).…”
Section: Environmental Implicationsmentioning
confidence: 98%
See 2 more Smart Citations
“…For the pristine PVDF membrane, the effective filtration area (i.e., the pore area on the membrane surface) is smaller than the total membrane surface area. For the TFC Janus membrane, however, the effective filtration area could be the total surface area of the polyamide layer and thus might be higher than the membrane surface area considering the crumpled morphologies of the polyamide layer. , This enhanced filtration area might explain the enhanced vapor flux. Other mechanisms, such as confined evaporation in the polyamide layer, might also contribute to the enhanced vapor flux.…”
Section: Results and Discussionmentioning
confidence: 99%